Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw pada Pembelajaran IPA Kelas V SD Negeri Suka Menang - Listia Nurbaiti; Ahmad Gasdy Prananosa; Tri Juli Hajani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the student's IPA learning outcomes after applying the Cooperativ Tipe JIGSAW model for class V SD Negeri Suka Menang. The method used is in the form of an experiment with an experimental design used one-group pre-test and post-test. In this study, one sample class was used, namely all fourth grade students of SD Negeri Suka Win, totaling 20 students. The data collection technique used is a test technique. The collected data were analyzed using the z-test. Based on the results of data analysis with a significant level of = 5% and dk = 19, it shows the magnitude of Zcount = 7,62 and Ztable = 1.64 (Zcount>Ztable). Thus, it can be concluded that the IPA learning outcomes of V grade students of SD Negeri Suka Menang after the implementation of the Cooperativ Tipe JIGSAW significantly completed. Keywords: Application, JIGSAW, IPA,